2022
DOI: 10.3390/ijerph19095586
|View full text |Cite
|
Sign up to set email alerts
|

At Home and on the Brink: U.S. Parents’ Mental Health during COVID-19

Abstract: Though the COVID-19 pandemic required significant changes and adaptations for most Americans, parents faced acute challenges as they had to navigate rapidly changing schooling and child care policies requiring their children to spend more time at home. This study examines the effects of COVID-19 school and workplace policies as well as environmental and economic characteristics on parental mental health, worry, hopelessness, and anxiety. Using data from four waves of the Socio-Economic Impacts of COVID-19 Surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…This may have been especially true for this study's participants given that they were all women with young children. Many participants noted that household and childcare duties were traditionally women's responsibilities regardless of whether they had a domestic partner, highlighting the disproportionate caregiving burden for women in the U.S. [13]. Women in our study were unable to optimally address their health issues despite wanting to do so and being motivated to do so, due to the need to manage competing priorities at home, including childcare, often with minimal support.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…This may have been especially true for this study's participants given that they were all women with young children. Many participants noted that household and childcare duties were traditionally women's responsibilities regardless of whether they had a domestic partner, highlighting the disproportionate caregiving burden for women in the U.S. [13]. Women in our study were unable to optimally address their health issues despite wanting to do so and being motivated to do so, due to the need to manage competing priorities at home, including childcare, often with minimal support.…”
Section: Discussionmentioning
confidence: 94%
“…For women in our study, the interplay of childcare, household responsibilities and health issues led to cumulative stressors, which was overwhelming and contributed to emotional distress. Prior studies have similarly found that parents have been facing high levels of psychological distress and exhaustion during the COVID-19 pandemic, in part due to prolonged social isolation and increased care demands [13,20].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations